Corpos e ambivalências : uma etnografia na praia de Camburi na cidade de Vitória/ES - Herrera, Rodrigo Esteban Gutiérrez (2018)
The main objective of the dissertation is to interpret the body understandings by the goers (individuals who realizes corporal practices) of the Camburi beach located in the city of Vitória/ES. These body understandings are crossed by a diversity of discourses developed in the modernity and high modernity. Thus, issues related to health and aesthetics are analyzed. The research was developed through an ethnography on the Camburi Beach where semi-structured interviews were also carried out, from which different categories of analysis were developed: health, sociability and aesthetics. The analyzes of the practices resulted in a direct relationship with health motivations, thus aiming a permanent need for feelings of wellbeing as it happens in relation to the different types of consumption in which they stand out in the beach space, physical activity and leisure are highlighted.